Numerical Study of Nanoparticle Coagulation in Non-Road Diesel Engine Exhaust Based on the Principle of Split-Stream Rushing - Yuchen Guo; Pei Wu; He Su; Jing Xue; Yongan Zhang; Peiyan Huang (Energies)
Diesel engines employed in non-road machinery are significant contributors to nanoparticulate matters. This paper presents a novel device based on the principle of split-stream rushing to mitigate particulate matter emissions from these engines. By organizing and intensifying the airflow movement of the jet in the rushing region, the probability of collisions between nanoparticles is enhanced. This accelerates the growth and coagulation of nanoparticles, reducing the number density of fine particulate matter. This, in turn, facilitates the capture or sedimentation of particulate matter in the diesel engine exhaust aftertreatment system. The coagulation kernel function tailored for diesel engine exhaust nanoparticles is developed. Then, the particle balance equation is solved to investigate the evolution and coagulation characteristics. Afterwards, three-dimensional numerical simulations are performed to study the flow field characteristics of the split-stream rushing device and the particle evolution within it. The results show that the device achieves a maximum coagulation efficiency of 59.73%, increasing the average particle diameter from 96 nm to 121 nm. The particle number density uniformity index exceeded 0.93 in most flow regions, highlighting the effectiveness of the device in ensuring consistent particle distribution.